Community-Based Tourism Mangrove Swamp Ecotourism Based on Maqashid Sharia - Galuh Nashrulloh Kartika MR; Rozzana Erziaty; Akhmad Hulaify; Yarna Hasiani; Ariyadi Ariyadi (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Having a wealth of potential mangrove resources, Pagatan Besar village has the opportunity to develop a sustainable ecotourism sector. This development must be directed at minimizing negative impacts on the environment and ensuring that the welfare of local communities increases. This research aims to find strategies for developing mangrove swamp ecotourism potential in Pagatan Besar village by optimizing the role of the Community based on Maqashid al Syari'ah. Qualitative research using a case study method in the mangrove swamp ecotourism area found that the strategy applied in developing the tourism potential of the mangrove swamp ecotourism area in the region was to implement a transparent accounting system to manage ecotourism income and expenditure, forming a special team to allocate initial investment funds and on the necessary infrastructure, maintaining the security and comfort of tourists with regular security audits, updating the security system through technology such as CCTV cameras. Optimizing the role of the Community is carried out by involving residents in skills training programs in the mangrove ecotourism sector, regular meetings for input and ideas, overcoming gaps in cultural and religious values with cross-sector consultation groups involving religious, cultural and village government leaders in the integration of Maqashid values al Syari'ah in the ecotourism plan, increasing environmental awareness through healthy environmental education for tourists and residents in daily ecotourism activities.